STRATEGI PENINGKATAN PEREKONOMIAN KELUARGA NELAYAN PESISIR: PERAN PEREMPUAN DALAM PEMANFAATAN DIGITAL MARKETING - Juliedi Manuel Palenewen; Oktaviani Ramenusa; Pradipta Mandasari Parasan (Al-Buhuts, 2026)
The well-being of coastal communities in Indonesia continues to face various challenges due to limited access to technology and low utilization of digital marketing in the economic activities of fishing households. This study aims to analyze the impact of women’s role in the use of digital marketing on the household income of fishing families on Lembeh Island, Bitung City. The study employed a quantitative approach using a survey method involving 90 respondents selected through purposive sampling. The data were analyzed using simple linear regression with the aid of SPSS. The results show that women’s role in the use of digital marketing has a positive and significant effect on fishing families’ income (β = 0.606; t = 24.656; p < 0.05; R² = 0.874), indicating that 87.4% of the variation in family income can be explained by this variable. These findings expand the body of research on the economic empowerment of coastal communities through the integration of women’s roles and the use of digital technology in small island regions vulnerable to economic uncertainty. The novelty of this study lies in its empirical examination of the relationship between gender roles, digital marketing, and the economic vulnerability of coastal communities—a topic that has rarely been studied quantitatively in Indonesia. This study confirms that strengthening the digital capacity of coastal women can be a key strategy in improving the well-being of fishing families. Therefore, policies are needed to support the improvement of digital literacy, community-based marketing training, and the provision of technological infrastructure to drive sustainable local economic transformation.